Island and Mobility in the Face of Climate Change: Robert Smithson's Floating Island - Lee, Jaeeun (Archīum Ateneo, 2024)
This essay aims to examine the entropic landscape in motion that appears in Floating Island by Robert Smithson, a distinguished earth artist active in the 1970s. Floating Island was a temporary artificial mobile island made with earth, rocks, native trees, and shrubs, towed by a tugboat around Manhattan Island. Smithson attempted to combine his artistic imagination with the theory of science, particularly entropy, a pivotal concept in the second law of thermodynamics while also developing an original idea of his own, namely “dialectics of entropic change” that combined entropy with dialectic. He believed that the dialectic could go beyond entropy and reach toward a continuous ever-changing process, which means that “destruction caused by entropy” is not the end of objects as static or discrete but fluctuating and entangled processes. Smithson’s concept relates to open systems that are antithetical to closed systems that succumb to entropy. Against this backdrop, this paper explores the meanings of entropic landscape in motion based on Floating Island, for which the artist drew inspiration from dreaming of a “mobile” or “moving” Central Park from the perspective of the dialectic of entropic change. Through the island’s movement, which remains elusive from a static viewpoint of a viewer from a central location like Manhattan, Smithson demonstrates how the geopolitical significance and values traditionally ascribed to the city by dichotomous thinking are not immutable truths. The mobility integrated into Floating Island, grounded in the dynamic vitality of nature, draws upon Smithson’s innovative dialectics on entropic change, blurring the boundaries between center (life, structure, city, etc.) and periphery (death, debris, island, etc.) through the set of relationships. This offers a meaningful framework for contemplation on sustainability that transcends the boundaries of dichotomous thinking, particularly resonant in today’s era confronted with climate change.